AN EVOLUTIONARY PERSPECTIVE: FROM COMPUTERS TO ANXIETY OF COMPUTER USERS - Keskin, Halit; Imamoglu, Salih Zeki; Senturk, Hayat Ayar; Kayman, S. Serda (FUTURE ACAD, 2019)
In today's technology oriented world, it is almost impossible to be isolated from the use of technology in daily life. Although these great developments in computer-based technologies make our lives easier, these rapid changes are also inevitable to intimidate some of the users. From the moment computer entered our lives, computer-based technologies have attracted many researchers from a variety of disciplines. However, the term computer anxiety, which is defined as a feeling of fear and apprehension that emerges when an individual is using a computer or thinking about the possibility of using a computer, has rarely been addressed in the literature. Therefore, we know little about how computer anxiety is defined and relates to other concepts. Accordingly, in this study, we will argue i) how the computer anxiety concept can be defined and conceptualized for future empirical investigations; ii) how computer anxiety can be developed, and iii) what can be the possible consequences of computer anxiety. (C) 2019 Published by Future Academy www.FutureAcademy.org.UK
Keywords: Anxiety; computer anxiety; computer users; antecedents and consequences of computer anxiety; SELF-EFFICACY; EXPERIENCE; ATTITUDES; GENDER; DETERMINANTS; Business & Economics